Anais Do XL Simpósio Brasileiro De Telecomunicações E Processamento De Sinais 2022
DOI: 10.14209/sbrt.2022.1570808562
|View full text |Cite
|
Sign up to set email alerts
|

Sensoriamento Espectral com Receptor por Conversão Direta sob Ruído Impulsivo

Abstract: Resumo-O ruído impulsivo pode ser extremamente prejudicial à operação de sistemas eletrônicos em geral, e de sistemas de comunicação em particular, como é o caso dos sensores de espectro em redes de rádios cognitivos. O artigo avalia o desempenho do sensoriamento espectral sob influência de ruído impulsivo. Dois receptores são comparados: um receptor convencional, que não considera aspectos de implementação prática, e um receptor por conversão direta (direct-conversion receiver, DCR) que leva em conta tais asp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
(33 reference statements)
1
2
0
Order By: Relevance
“…Conventional and DCR-based receiver models are used to compare the performances of the energy detector (ED), the absolute value cumulating (AVC) detector, the Gerschgorin radii and centers ratio (GRCR) detector, the Gini index detector (GID), the Pietra-Ricci index detector (PRIDe) and the locally most powerful invariant test (LMPIT) detector. This work merges and extends the research reported in [17] and [27]. The merged part refers to the assessment of the conventional and the DCR-based receiver models under SαS and αSG noise.…”
Section: B Contributions and Organization Of The Articlesupporting
confidence: 60%
See 2 more Smart Citations
“…Conventional and DCR-based receiver models are used to compare the performances of the energy detector (ED), the absolute value cumulating (AVC) detector, the Gerschgorin radii and centers ratio (GRCR) detector, the Gini index detector (GID), the Pietra-Ricci index detector (PRIDe) and the locally most powerful invariant test (LMPIT) detector. This work merges and extends the research reported in [17] and [27]. The merged part refers to the assessment of the conventional and the DCR-based receiver models under SαS and αSG noise.…”
Section: B Contributions and Organization Of The Articlesupporting
confidence: 60%
“…The performance of spectrum sensing when impaired by impulsive noise is also evaluated in [27]. Two receivers are compared: a conventional one, which does not consider practical implementation aspects, and a DCR model that takes these aspects into account.…”
Section: A Related Researchmentioning
confidence: 99%
See 1 more Smart Citation